Current approaches to the verification of bacterial vaginosis diagnosis and treatment tactics - Pestrikova T.Yu; Yurasova E.A; Kotelnikova A.V; Knyazevа T.P (LCC «Medicine-Inform», 2018)
Current approaches to the verification of bacterial vaginosis diagnosis and treatment tactics Pestrikova T.Yu., Yurasova E.A., Kotelnikova A.V., Knyazevа T.P. Far Eastern State Medical University The prevalence of bacterial vaginosis varies widely. Its incidence amounts to 35% of all gynecological pathologies; 10-30% - in pregnant women; 20-60% - in patients treated for sexually transmitted infections. The article presents the current data on epidemiology, etiology, diagnosis, and treatment of this pathology. It is emphasized that the use of the real-time polymerase chain reaction method is reasonable for the diagnosis of bacterial vaginosis. During the treatment, special attention is paid to the use of a combination of metronidazole + miconazole. This drug is effective for the treatment of bacterial vaginosis, vulvovaginal candidiasis, mixed vaginitis infections. The combined drug (metronidazole + miconazole) is effective against aerobic and anaerobic microbial agents, including Gardnerella vaginalis, and against Candida albicans, Trichomonas vaginalis, Entamoeba histolytica, etc., which makes it possible to use it for the treatment of both bacterial vaginosis and its combination with candidal vulvovaginitis. Key words: bacterial vaginosis, real-time polymerase chain reaction, candidiasis vulvovaginitis, combined drug (metronidazole + miconazole). For citation: Pestrikova T.Yu., Yurasova E.A., Kotelnikova A.V., Knyazeva T.P. Current approaches to the verification of bacterial vaginosis diagnosis and treatment tactics // RMJ. 2018. № 2(I). P. 48-53.